Central banks' interest rate and international trade in BRIC countries: Agriculture vs machinery industry? - Konstantin Borodin; Anton Strokov (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
The paper investigates interrelations between the dynamics of national central banks' interest rates and international trade within the BRIC countries. It shows that countries with lower interest rates experience growth of the share of machinery industry exports rather than agriculture and food products, and, on the contrary, in countries with higher interest rates the share of agriculture and food exports increases and the share of machinery industry products declines. The investigation has shown that a relative shift in the interest rate can affect the specialization of countries.
Keywords: F1; 330; Central banks' interest rate; Exports; Specialization